1992
DOI: 10.1177/088307389200700105
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Nevus Syndrome: Subgroup With Neuronal Migration Defects

Abstract: Epidermal nevus syndrome is one of the sporadic congenital hamartoses in which neurologic abnormalities have been frequently reported. We report two cases with severe primary brain involvement, seizures, mental retardation, and facial hemihypertrophy. We emphasize the superiority of magnetic resonance imaging over other radiographic studies in outlining the primary central nervous system anomalies associated with this syndrome. Although attempts were made to distinguish between several variants of epidermal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Whether ENS represents a single syndrome, or a variety of distinct entities, continues to be debated [Solomon and Esterly, 1975;El-Shanti et al, 1992;Schwartz, 2002]. In fact, ENS has also been referred to as linear sebaceous nevus syndrome, Feuerstein-Mims syndrome, Schimmelpenning-FeuersteinMims syndrome, Schimmelpenning syndrome, nevus sebaceous of Jadassohn, Jadassohn's naevus phakomatosis, and Solomon syndrome [Zaremba, 1978;Gorlin, 1990Gorlin, , 2001OMIM 163200].…”
Section: Discussionmentioning
confidence: 98%
“…Whether ENS represents a single syndrome, or a variety of distinct entities, continues to be debated [Solomon and Esterly, 1975;El-Shanti et al, 1992;Schwartz, 2002]. In fact, ENS has also been referred to as linear sebaceous nevus syndrome, Feuerstein-Mims syndrome, Schimmelpenning-FeuersteinMims syndrome, Schimmelpenning syndrome, nevus sebaceous of Jadassohn, Jadassohn's naevus phakomatosis, and Solomon syndrome [Zaremba, 1978;Gorlin, 1990Gorlin, , 2001OMIM 163200].…”
Section: Discussionmentioning
confidence: 98%
“…4 Van de Warrenburg et al 15 included brain dysgenesis, cortical dysplasia, glial hamartomas, low-grade gliomas, hemimegalencephaly (usually ipsilateral to the nevus), and enlargement of the lateral ventricles. 15,43,45 Epilepsy was present in up to 67% of patients. 15 In their review of 12 LNSS patients, Lovejoy and Boyle 24 found that seizures usually began within the first year of life.…”
mentioning
confidence: 99%
“…He was developmentally delayed. ElShanti et al [5] reported two cases of ENS with severe primary cerebral development, seizures, mental retardation and facial hemihypertrophy. In case 1, MRI of the brain showed hemimegalencephaly, pachygyria and distension of left lateral ventricle; case 2 had left hemimegalencephaly and ipsilateral dilatation of the lateral ventricle and agyria.…”
Section: Discussionmentioning
confidence: 98%